Sensory Acceptability and Characteristics of Cinnamon Roll Bread with Pineapple Puree (Ananas comosus L.) Substituted with Taro Flour - Suleman, Dininurilmi Putri; Sari, Mulyani Mukti; Rochmah, Alfi Nur; Zulfa, Fitriyah (Journal of Agri-Food Science and Technology, 2025)
The development of functional food can be applied to bakery products, it is hoped that bread can provide health effects for the body through the addition of food ingredients or substitution of highly nutritious foods. In this research, innovations were made in making cinnamon rolls with local food ingredients other than wheat flour, namely taro flour, pineapple puree, and cinnamon. This research contributed to produce cinnamon roll products that are favored by the public and have good nutritional value based on organoleptic and physicochemical characteristics. The research method used was a Completely Randomized Design (CRD) consisting of 5 levels of taro flour treatment, namely 0%, 40%, 60%, 80%, and 100%. Each sample will be analyzed through organoleptic tests using hedonic method to determine the most preferences formulation by panelists. The most preferences formulation will be characterized physicochemical, including final volume, texture, moisture content, starch content, and antioxidant activity. The results of organoleptic tests showed that the most liked bread by panelists was cinnamon roll bread substituted with 40% taro flour. Physicochemical characters show that cinnamon roll bread with 40% taro flour has a final volume 63.17 cm2, hardness texture 5.65 N, moisture content 18.50%, starch content 44.97%, and antioxidant activity 16.32%.